2018
DOI: 10.1039/c7sc04759b
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of highly Lewis acidic diborane(4) towards pyridine and isocyanide: formation of boraalkene–pyridine complex and ortho-functionalized pyridine derivatives

Abstract: The reaction of pinB-BMes2 with Xyl-NC and pyridine results in the formation of a pyridine-coordinated boraalkene that exhibits an intense color. In the presence of an excess of pyridine, the ortho C–H bond of pyridine was selectively functionalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 121 publications
0
22
0
Order By: Relevance
“…Communications analysis,a nd the elemental analysis all supported the formation of 17.T he reaction between 1 and 2equiv of Xyl À NC led to the formation of 18,i nw hich Xyl À NC coordinates to 17.B ased on the X-ray crystallographic analysis (Figure 5), coordination of XylÀNC to 17 directly affords 18,a sc onfirmed by independent experiment for the formation of 18 by ar eaction of 17 with 1equiv of Xyl À NC. The 1 H, 11 B, and 13 CNMR spectra of 18 suggested the presence of asingle diastereoisomer, which is most likely due to the steric repulsion between two o-tolyl groups.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Communications analysis,a nd the elemental analysis all supported the formation of 17.T he reaction between 1 and 2equiv of Xyl À NC led to the formation of 18,i nw hich Xyl À NC coordinates to 17.B ased on the X-ray crystallographic analysis (Figure 5), coordination of XylÀNC to 17 directly affords 18,a sc onfirmed by independent experiment for the formation of 18 by ar eaction of 17 with 1equiv of Xyl À NC. The 1 H, 11 B, and 13 CNMR spectra of 18 suggested the presence of asingle diastereoisomer, which is most likely due to the steric repulsion between two o-tolyl groups.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[3p, 6] Bis(pinacolato)diborane (B 2 pin 2 ), which is stabilized by pp-pp interactions from four adjacent oxygen atoms,h as been widely used for transition-metal-catalyzed borylations of organic molecules. [8] Thea bsence of heteroatoms at one of the two boron atoms renders this molecule highly electrophilic.Infact, pinBÀBMes 2 reacts with tert-butylisocyanide leading to cleavage of the NCt riple bond, [8] with CO to provide aC O-coordinated boraalkene, [8] with alkynes to form diborylalkenes, [9] with 2,6-dimethylphenylisocyanide to furnish a1 ,2-oxaboretane ring, [10] with pyridine to give C À Hf unctionalized pyridines, [11] and with electrons to afford the corresponding radical anion. [8] Thea bsence of heteroatoms at one of the two boron atoms renders this molecule highly electrophilic.Infact, pinBÀBMes 2 reacts with tert-butylisocyanide leading to cleavage of the NCt riple bond, [8] with CO to provide aC O-coordinated boraalkene, [8] with alkynes to form diborylalkenes, [9] with 2,6-dimethylphenylisocyanide to furnish a1 ,2-oxaboretane ring, [10] with pyridine to give C À Hf unctionalized pyridines, [11] and with electrons to afford the corresponding radical anion.…”
mentioning
confidence: 99%
“…[23] Comparison with the corresponding bis(IMes) adduct, B 2 Cl 4 (IMes) 2 (Figure 1), shows much shorter BÀBa nd BÀCb onds in B 2 Cl 4 (IMes) (1.719(4) and 1.619(4) ,r espectively)v ersus B 2 Cl 4 (IMes) 2 (1.760(4) and 1.645(3), 1.646(3) ,r espectively)a se xpected for the lower coordination number.I nr ecent years sp 2 -sp 3 -diboranes have gained in popularity due to their potential as sourceso fanucleophilic boryl moiety [2] and numerous examples have now been structurally characterized. [38] However,b esides B 2 Br 4 (CAAC B ), [23] B 2 Cl 4 (IMes) is only the second example of a crystallographically characterized tetrahalodiborane(4) monoadduct.…”
Section: X-ray Crystallographic Analysesmentioning
confidence: 99%
“…11 B NMR spectroscopic analysis revealed that a new peak with a chemical shift of 8.8 ppm appeared upon mixing B 2 pin 2 with Py2SNa, suggesting the formation of an anionic diboron species (Figure S7).Meanwhile, it was observed that, both 1 H NMR and13 C NMR signals of Py2SNa were shifted with 1.0 equivalent of B 2 pin 2 added, confirming the formation of a new boryl species. Considering the ease with which diboronate esters can react with pyridine type bases to form the corresponding Lewis base adducts,40,[61][62][63] it was postulated therefore that a Lewis acid-base adduct formed between Py2Sand pin 2 was responsible for the observed redshift.…”
mentioning
confidence: 99%